Blockchain: How shipping industry is dealing with the ultimate technological leap. (March 2020) - Bavassano, Giorgio; Ferrari, Claudio; Tei, Alessio
Abstract: Despite its historical resilience to innovation, several novel technologies (e.g. IoT, AIS data, and automation) have recently been introduced in the maritime sector: the majority of them represents incremental changes in respect to current practice. Nevertheless, a few of these novel solutions could represent radical game changers for the whole shipping business. Among the latter category, blockchain registers a particular role, given the possibility for smoothening administrative problems, providing new ways to achieve secure and frictionless transactions at a global level. Despite the importance of such innovation, most of the published studies have just focused on technical aspects, while the adoption and implementation processes are far to be clarified since there is not a clear understanding on the potential effects of blockchain on shipping and logistics actors, especially at local level. The proposed study aims at filling this gap, providing insights that might help to better understand: i) which are the actors that impact the most on the blockchain implementation (and related potential frictions), and ii) the difference among alternative initiatives currently present on the market. In order to achieve these twofold aim, the study uses a triangulation approach, mixing literature and media reports research with both web-based research on main initiative characteristics and expert opinions. The proposed study defines that regulators and public authorities might potentially represent the main barrier to the full implementation of the block chain technology, especially due to a missing market standard.